The transit of Venus - Hazzard, Shirley, 1931-2016 (New York, N.Y. : Playboy Paperbacks, 1981)
From the 1950s to the 1980s, in Sydney, London, New York, and Stockholm, Caro and Grace Bell--beautiful Australian orphans--make their ways with the husbands and lovers whom they love in duty and passion.
Original edition: New York : Viking Press, 1980.
Keywords: Sisters -- Fiction; Orphans -- England -- Fiction; England -- Fiction